Association between Reactive Attachment Disorder/Disinhibited Social Engagement Disorder and Emerging Personality Disorder: A Feasibility Study - Khadija Mirza; Gracia Mwimba; Rachel Pritchett; Claire Davidson (The Scientific World Journal)
A systematic review of reactive attachment disorder (RAD)/disinhibited social engagement disorder (DSED) in adolescence highlighted that young people with the disorder had indiscriminate friendliness with difficulties in establishing and maintaining stable relationships. Most reported experiences of rejection. We were struck by similarities between the above and features of emergence of personality disorders (EPD). This feasibility study aimed to determine best ways of recruiting and retaining vulnerable young people and the proportion of participants with RAD/DSED who might have emerging borderline personality disorder (EBPD). Participants were referred to the study by their treating clinicians from local mental health teams. Results showed strong association between RAD/DSED and EBPD. Participant characteristics showed high levels of out of home placements, early termination of school careers, suicide attempts, quasipsychotic symptoms, and multiagency involvements. They experienced the project as an opportunity to talk about relationships and reported that they would like more of this in usual clinical contacts. They all agreed to be contacted for future studies. Previous studies have shown that early detection and treatment of emergent personality traits can alter trajectory. Future research will continue to explore these trajectories, explore detection of vulnerability factors, and evaluate interventions.